Correction: Diets Containing Sea Cucumber (Isostichopus badionotus) Meals Are Hypocholesterolemic in Young Rats - Olivera-Castillo, Leticia; Davalos, Alberto; Grant, George; Valadez-Gonzalez, Nina; Montero, Jorge; Barrera-Perez, Hirian Alonso Moshe; Chim-Chi, Yasser; Olvera-Novoa, Miguel Angel; Ceja-Moreno, Víctor; Acereto-Escoffie, Pablo; Rubio-Piña, Jorge; Rodriguez-Canul, Rossanna (PLOS ONE, 2015)
null